2016
DOI: 10.1016/j.renene.2015.07.082
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen rich gas production from catalytic gasification of biomass

Abstract: a b s t r a c tProduction of hydrogen rich gas from gasification of biomass was studied at bench-scale using oxygen as the gasifying agent. A series of experiments were performed to investigate the effects of different operating parameters on the performance of the gasification process. These included the oxygen to fuel equivalence ratio (0.12e0.4), reaction temperature (700e850 C), reaction residence time (45e120 min), and catalyst type. The catalysts selected are marly clay, calcium hydroxide, dolomite, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
44
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 118 publications
(47 citation statements)
references
References 23 publications
2
44
0
1
Order By: Relevance
“…The catalysts selected are USY zeolite, dolomite, CaO, granulated slag, red brick clay, olivine, and cement kiln dust. The results demonstrate that the cement kiln dust and calcium hydroxide are more effective for increasing the gas yield and decreasing the char yield [8,10].…”
Section: Residence Timementioning
confidence: 99%
See 3 more Smart Citations
“…The catalysts selected are USY zeolite, dolomite, CaO, granulated slag, red brick clay, olivine, and cement kiln dust. The results demonstrate that the cement kiln dust and calcium hydroxide are more effective for increasing the gas yield and decreasing the char yield [8,10].…”
Section: Residence Timementioning
confidence: 99%
“…Due to environmental and technical difficulties associated with burning biomass, innovative processes should be developed to utilize biomass [5,[8][9][10]. Developing more effective techniques to utilize biomass will reduce the disposal problem and create profits.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In another research study, it was reported that gasification of cotton stalk at 850°C, with oxygen fuel ratio (0.12-0.4) in presence of Ca(OH) 2 yielded 45 % H 2 , and 33% CO (Hamad et al 2016). Gasification of woody biomass in fluidized bed using air as gasifying agent & fluidizing gas (with control flow rate) gave low calorific value syngas (Kim et al (2013 (Chen and Zhang 2015).…”
Section: Introductionmentioning
confidence: 97%